(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Recently, scalar damage models based on the micropolar continuum theory have been proposed, in order to represent the physically non-linear behaviour of quasi-brittle materials. Due to its regularization properties, widely investigated in elasto-plasticity, the micropolar theory represents a valid alternative for mitigating pathological phenomena that arise in the numerical simulations. In the last years, also the class of mesh-free methods have been shown to be capable to regularize the response of problems where localization occours. This paper investigates the coupling of micropolar damage models with mesh-free methods, with specific attention on the Element Free Galerkin (EFG) method. The micropolar theory is presented in a tensorial generalized form, and different scalar damage models are derived in a theoretical and computational unified framework for constitutive models. The computational aspects of the coupling between micropolar damage and mesh-free approach are also discussed, with specific attention on the implementation in the INSANE (INteractive Structural ANalysis Enviroment) system. Numerical simulations are presented in order to illustrate the proposed models.